1991
DOI: 10.1159/000125924
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor I: A Possible Metabolic Signal Involved in the Regulation of Female Puberty

Abstract: In both rats and primates, including humans, serum levels of insulin-like growth factor I (IGF-1) increase during the onset of puberty, suggesting a role for IGF-I in this process. We examined the ability of IGF-1 to affect the release of hypothalamic luteinizing hormone releasing hormone (LHRH) in prepubertal female rats. Our results indicate that IGF-I acts on the median eminence, which contains the highest density of type 1 IGF receptors in the brain, to elicit a dose-related increase in LHRH release. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
1
9

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(143 citation statements)
references
References 16 publications
6
127
1
9
Order By: Relevance
“…Thus, hGH could induce precocious puberty without changing growth rate in this Line. Under normal laboratory conditions, the age at vaginal opening is known to correlate nicely with body weight [30], suggesting that some metabolic factor signals the onset of puberty [30,31]. Line 2 transgenic female rats would be a good model for investigating that metabolic factor, if any, because growth promoting and puberty enhancing activities are separated in this animal model.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, hGH could induce precocious puberty without changing growth rate in this Line. Under normal laboratory conditions, the age at vaginal opening is known to correlate nicely with body weight [30], suggesting that some metabolic factor signals the onset of puberty [30,31]. Line 2 transgenic female rats would be a good model for investigating that metabolic factor, if any, because growth promoting and puberty enhancing activities are separated in this animal model.…”
Section: Resultsmentioning
confidence: 99%
“…Neurotrophic factors may also play a similar role, and I would like to propose the hypothalamic insulin-like growth factor-1 (IGF-1) system as a target for neuroendocrine disruption. My laboratory and others have shown that IGF-1 regulates GnRH release and gene expression, and that this is subject to developmental regulation [74,75,37]. The IGF-1 system is also steroid sensitive [75,48,101].…”
Section: Other Hypothalamic Neurotransmitter and Neurotrophic Factor mentioning
confidence: 97%
“…IGF-I is involved in modulating hypothalamus and pituitary functions [28,42,71,85,91,92]. Several biological actions induced by IGF-I on GnRH and gonadotropin have been elucidated by a number of in vitro studies [53,95].…”
Section: Igf-i and Hypothalamo-pituitary Functionmentioning
confidence: 99%